Expanding the Isotopic Toolbox: Applications of Hydrogen and Oxygen Stable Isotope Ratios to Food Web Studies - Vander Zanden, Hannah B.; Soto, David X.; Bowen, Gabriel J.; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2016)
The measurement of stable carbon (δ13C) and nitrogen (δ15N) isotopes in tissues of organisms has formed the foundation of isotopic food web reconstructions, as these values directly reflect assimilated diet. In contrast, stable hydrogen (δ2H) and oxygen (δ18O) isotope measurements have typically been reserved for studies of migratory origin and paleoclimate reconstruction based on systematic relationships between organismal tissue and local environmental water. Recently, innovative applications using δ2H and, to a lesser extent, δ18O values have demonstrated potential for these elements to provide novel insights in modern food web studies. We explore the advantages and challenges associated with three applications of δ2H and δ18O values in food web studies. First, large δ2H differences between aquatic and terrestrial ecosystem end members can permit the quantification of energy inputs and nutrient fluxes between these two sources, with potential applications for determining allochthonous vs. autochthonous nutrient sources in freshwater systems and relative aquatic habitat utilization by terrestrial organisms. Next, some studies have identified a relationship between δ2H values and trophic position, which suggests that this marker may serve as a trophic indicator, in addition to the more commonly used δ15N values. Finally, coupled measurements of δ2H and δ18O values are increasing as a result of reduced analytical challenges to measure both simultaneously and may provide additional ecological information over single element measurements. In some organisms, the isotopic ratios of these two elements are tightly coupled, whereas the isotopic disequilibrium in other organisms may offer insight into the diet and physiology of individuals. Although a coherent framework for interpreting δ2H and δ18O data in the context of food web studies is emerging, many fundamental uncertainties remain. We highlight directions for targeted research that will increase our understanding of how these markers move through food webs and reflect ecological processes.